A Secure Cloud-Edge-Shared Storage System for Data Sharing and Searching on Edge Servers - Swetha, D. Naga; Tellur, Anil (International Journal of Psychosocial Rehabilitation, 2020)
Ensuring and preserving the data privacy on the cloud and offering security for data sharing between IoT devices and users for pointed of data between the cloud and users on edge servers is made possible with Cloud-Edge Shared Storage System (CESSS). This system effectually diminishes the computing load of IoT devices and users by allocating computation-intensive encryption and decryption algorithms to edge servers. Substantial reduction of the computing and communication overhead for generating keyword search trapdoors is beneficial with reference to maintaining the privacy of IoT devices and user’s private keys and attaining further protected or resourceful data sharing and data searching.